Thermal Model for Transformer Lifetime Prediction Using Simulation Method - Nasir Abdunabi Issa Shwaikat; Jamal Ali Ramadan Dofan; Majdi Farag Mohammed El Bireki; Khalid Yahya; Ferass A. Muftah Saad (African Journal of Advanced Pure and Applied Sciences, 2025)
This paper presents simulation technique for life assessment of the insulation of the power transformer. Load and ambient temperatures are two important factors that influence the hot spot of transformers. The transformer hot spot temperature is one of the most critical parameter in determining the life of transformer paper insulation. The simulation (Matlab Software Package) is based on related international standards as the IEC 60076-7:2005 loading guide method. Load and ambient temperatures of the transformer obtain from General Electrical Company and meteorology office of Libya are used as the input for the simulation together with transformer parameters from heat run test. Hottest spot temperature and loss-of-life are calculated. Lifetime of transformer is predicted.